Peer Tutoring in PBL with Ethnomathematics Approach to Improve Students' Comprehension Ability: A Gender Perspective - Nining Yuningsih; Dayat Hidayat (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2025)
Mathematical understanding is essential for supporting students in solving problems, thinking logically, and developing self-confidence. However, many students at Madrasah Aliyah continue to experience difficulties in understanding mathematical concepts. These difficulties arise not only from low learning interest, the dominance of rote memorization, and the abstract nature of mathematics, but also from the lack of contextual relevance that connects mathematical ideas to students’ cultural experiences. To address these issues, a peer tutoring strategy within ethnomathematics-based problem-based learning (PBL) was implemented. This approach allows students to collaborate with peers while engaging with culturally relevant contexts, making learning more meaningful. This study aims to examine the implementation of the strategy and evaluate its effect on students’ mathematical understanding in terms of gender. A mixed-methods approach with an embedded design was employed, in which quantitative data served as the primary component for analyzing treatment effects, while qualitative data from observations and interviews were used to support and explain gender-related differences in the quantitative findings. The research involved 32 students at a Madrasah Aliyah in Bandung. Data were collected through questionnaires, tests, observations, interviews, and documentation; quantitative data were analyzed using two-way ANOVA and correlation tests, and qualitative data through triangulation. The two-way ANOVA results showed a significant main effect of the peer tutoring strategy in ethnomathematics-based PBL on mathematical understanding, as well as a significant interaction between learning strategy and gender, with female students outperforming male students. Improvements in self-confidence and cultural awareness were qualitatively observed rather than measured formally. These findings indicate that ethnomathematics-based PBL with peer tutoring offers a contextual and collaborative approach that effectively enhances students’ mathematical understanding.